Utilizing artists’ sense of place from environmental aesthetic experiences in natural resources conservation planning in Masbate City, Philippines - Asilum, Jofer B. (School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Rooted in the growing discourse on the applications of cultural ecosystem services in attaining sustainable development, this study evaluates artists' sense of place from environmental aesthetic experiences as an approach to natural resources conservation planning in Masbate City, the Philippines. Given that sense of place strengthens environmental values and influences support for conservation, this research investigates how artists' perceptions shaped by environmental aesthetics can inform conservation efforts, not only through their art, but also their potential roles as key actors in conservation planning. This study specifically aimed to 1) explain artists' sense of place, 2) examine how environmental aesthetics contribute to making a place aesthetically remarkable, 3) assess environmental factors influencing artists' sense of place, 4) analyze the relationship between artists' sense of place and involvement in conservation, and 5) explore institutional arrangements for integrating artists' sense of place from environmental aesthetic experiences into natural resources conservation planning.